Prior exercise and postprandial incretin responses in lean and obese individuals - Heden, Timothy D. (2013)
PURPOSE: The incretin hormones glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) help regulate postprandial triacylglycerol (TAG) and insulin concentrations, but the effects of acute aerobic exercise on GLP-1 or GIP responses are unclear. The purpose of this study was to determine if reductions in postprandial TAG and insulin with exercise are associated with GLP-1 and GIP responses. METHODS: Thirteen normal-weight (NW) and 13 Obese (Ob) individuals participated in two, 4-d trials in random order including an exercise (EX) and a no exercise (NoEX) trial. Diet was controlled during both trials. The EX trial consisted of 1 h of treadmill walking (55–60% of VO(2)peak) during the evening of day 3 of the trial, 12 h prior to a 4 h mixed meal test on day 4, during which frequent blood samples were taken to assess postprandial lipemia, glycemia, insulin, c-peptide, GIP, and GLP-1 responses. Insulin secretion was estimated using the Insulinogenic Index and insulin clearance was estimated using the ratio of insulin to c-peptide. RESULTS: Postprandial TAG’s were 29% lower after EX in Ob individuals (P<0.05) but were not significantly altered in NW individuals (P>0.05). The drop in postprandial high-density lipoprotein cholesterol was attenuated with EX in Ob individuals (P<0.05). Insulin responses were 14% lower after EX in Ob individuals (P<0.05), and this was associated with reduced insulin secretion (P<0.05), with no change in insulin clearance (P>0.05). Glucose, c-peptide, GIP, and GLP-1 were not different between trials. CONCLUSION: A 1 h bout of moderate intensity aerobic exercise the night prior to a mixed meal attenuates TAG and insulin responses in Ob, but not NW, individuals, an effect not associated with altered GLP-1 or GIP responses.